A study on customer relationship management in the Life Insurance Corporation of India with special reference to Tamil Nadu. (5th February 2023) - Beula, D. Sahaya; Velmurugan, V.P.; Janardhanan, K.A.
The study has focused on the customer relationship management (CRM) system in the life insurance sector of India. The study revealed the technical progress of India's insurance industry, especially in Tamil Nadu. The deployment of CRM systems in LIC and other private insurance sectors in India was analysed using primary data. India is a populous, diverse country. Life insurers can grow in unused markets. LIC previously dominated the Indian life insurance market, thus buyers had few options. So, private life insurance businesses emerged, and consumers can now readily separate LIC and other private insurance sectors. However, the number of respondents is limited to 51 respondents in this paper, which undermines the external and internal validity of the paper. In some circumstances, it's hard to understand the specific conclusion with real findings. Indian life insurance varies. The insurance market relies on medical and life histories. Life insurance sectors have so much information about their customers and sometimes they cannot properly handle all the data accordingly.